Analisis Perbandingan Enkripsi File Teks Berformat .txt dan .docx Menggunakan Algoritma AES - Kennardy Andrew Limartha; I Gede Arta Wibawa (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2025)
In this research, the Advanced Encryption Standard (AES) algorithm is used to encrypt text files. Data stored in various formats has the potential to cause the size of the data on the data storage device to become large and does not necessarily guarantee the security of the data. One method of data security is to encrypt data. This research utilizes data in text file format with data types in the form of